Gaudibility as a predictor of quality of life and happiness in students of higher technological institutes in Chiclayo, Peru - Davila, Julio Adrian Villegas (Edelweiss Applied Science and Technology, 2026)
This study aimed to analyze whether gaudibility, understood as the set of skills, beliefs, and habits that facilitate enjoyment, predicts quality of life and happiness in students from higher technological education institutions in Chiclayo, Peru. A quantitative, non-experimental, cross-sectional, and associative–predictive design was adopted. The sample consisted of 510 students aged 15 to 18 years, selected through probabilistic simple random sampling. Gaudibility was assessed using the Gaudibility Scale, happiness with the Lima Happiness Scale, and quality of life with the Olson and Barnes Quality of Life Scale. Data were analyzed using Spearman’s rho and regression model fit tests. The results showed positive and statistically significant correlations between gaudibility and quality of life (ρ = 0.2433; p < 0.001), as well as between gaudibility and happiness (ρ = 0.3901; p < 0.001). It is concluded that gaudibility is a relevant predictor of subjective well-being in this population. These findings suggest that strengthening enjoyment-related competencies may be an effective strategy for mental health promotion in educational settings.